A multicenter retrospective comparison of induction chemoimmunotherapy regimens on outcomes in transplant‐eligible patients with previously untreated mantle cell lymphoma. Issue 3 (24th May 2019) - Ng, Zi Yun; Bishton, Mark; Ritchie, David; Campbell, Robert; Gilbertson, Michael; Hill, Kate; Ratnasingam, Sumita; Schwarer, Anthony; Manos, Kate; Shorten, Sophie; Ng, Melissa; Nelson, Niles; et al.
Abstract: Mantle cell lymphoma (MCL) is an uncommon and typically aggressive form of lymphoma. Although often initially chemosensitive, relapse is common. Several induction and conditioning regimens are used in transplant‐eligible patients, and the optimal approach remains unknown. We performed an international, retrospective study of transplant‐eligible patients to assess impact of induction chemoimmunotherapy and conditioning regimens on clinical outcomes. We identified 228 patients meeting inclusion criteria. Baseline characteristics were similar among the induction groups except for some variation in age. The type of induction chemoimmunotherapy received did not influence overall response rates (ORRs) (0.43), progression‐free survival (PFS) ( P > .67), or overall survival (OS) ( P > .35) on multivariate analysis (PFS and OS). Delivery of autologous stem cell transplant (ASCT) was associated with favorable PFS and OS (0.01) on univariate analysis only; this benefit was not seen on multivariate analysis—PFS (0.36) and OS (0.21). Compared with busulfan and melphalan (BuMel), the use of the carmustine, etoposide, cytarabine, melphalan (BEAM)–conditioning regimen was associated with inferior PFS (HR = 2.0 [95% CI 1.1‐3.6], 0.02) but not OS (HR = 1.1 [95% CI 0.5‐2.3], 0.81) on univariate analysis only. Within the limits of a retrospective study and modest power for some comparisons, type of induction therapy did not influence ORR, PFS, or OS for transplant‐eligible patients with MCL. International efforts are required to perform randomized clinical trials evaluating chemoimmunotherapy induction regimens.